Safety First–An Expected Utility Principle - Levy, Haim; Sarnat, Marshall (Journal of Financial and Quantitative Analysis, 1972)
The theory of choice under conditions of certainty has been extended by Von Neumann and Morgenstern [8], Friedman and Savage [5], Marschak [13], and others to conditions involving risk by assuming that individuals maximize their expected utility. The application of this theory to portfolio selection, to efficiency criteria, and to the explanation of the well-known phenomenon of diversification of assets has been carried further by Markowitz [11 and 12], Tobin [17], Samuelson [15], Sharpe [16], and Lintner [10], and more recently by Hadar and Russell [5] and Hanoch and Levy [8].